Urgensi Penerapan Teknologi Informasi Pada Sistem Surveilans Kesehatan Masyarakat : Urgency of Information Technology Implementation in Public Health Surveillance System - D Sitanggang, Hendra; Daswito, Rinaldi (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2023)
This editorial aims to describe the urgency and potential of applying information technology to public health surveillance systems. Health surveillance is closely related to the information generated and will be used for planning, implementation, and evaluation of public health efforts. This information must arrive on time to those who need it and can be utilized to prevent and control public health problems. It is necessary to apply information technology in the surveillance system to increase efficiency and productivity without eliminating the key role of humans. The application of information technology can also be a solution to the limitations of the surveillance system, especially in the timeliness of reports, the lack of routine publication of surveillance profiles, the lack of data analysis carried out, and the lack of analytical capabilities.